Postpartum Anxiety Levels and Neonatal Care Responses Among Primiparous Mothers: Postpartum Anxiety Levels and Neonatal Care Responses Among First-Time Mothers - Nurul Azizah; Mela Nailul Izza (Indonesian Journal on Health Science and Medicine, 2026)
General Background The puerperal phase triggers significant physiological, psychological, and social transitions that require structured clinical monitoring to prevent severe maternal affective disorders. Specific Background Primiparous women exhibit heightened vulnerability to postpartum anxiety and depression compared to multiparous mothers due to childbirth unfamiliarity. Knowledge Gap However, maternal psychological adaptive patterns remain under-examined when complicated by unexpected infant clinical vulnerabilities that mandate specialized neonatal care. Aims This case study evaluates maternal postpartum anxiety triggered by newborn health complications in a 26-year-old primigravida. Results Psychometric screening using the Depression Anxiety Stress Scales confirmed mild anxiety (score: 8) caused by excessive cognitive overthinking, structural adaptation difficulties, and initial caregiving unfamiliarity. Novelty The evaluation demonstrates that immediate modification of external stressors, such as reducing social media consumption alongside active family support, effectively minimizes postpartum stress. Implications Midwives must provide comprehensive, continuous, and long-term psychosocial interventions to secure optimal maternal-infant health outcomes. Keywords: Postpartum Anxiety, Primigravida, Neonatal Care, Maternal Psychology, Clinical Midwifery Key Findings Highlights Psychometric assessment via the Depression Anxiety Stress Scales identifies a mild anxiety baseline score of 8 in primiparous tracking. Sudden requirements for specialized newborn medical care serve as an immediate trigger for acute maternal cognitive overthinking. Combining targeted social media reduction with consistent familial assistance actively minimizes postpartum emotional distress.